2013
DOI: 10.1136/bcr-2012-008505
|View full text |Cite
|
Sign up to set email alerts
|

Angina bullosa haemorrhagica

Abstract: Angina bullosa haemorrhagica is the term used to describe benign subepithelial oral mucosal blisters filled with blood that are not attributable to a systemic disorder or haemostatic defect. It is a very rare condition. Elderly patients are usually affected and lesions heal spontaneously without scarring. The pathogenesis is unknown, although it may be a multifactorial phenomenon. Trauma seems to be the major provoking factor and long-term use of steroid inhalers has also been implicated in the disease. We pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 11 publications
(6 reference statements)
1
19
0
8
Order By: Relevance
“…As Kirtschig and Happle pointed out, the term ABH is misleading because most bullae arise in the oral cavity and are not consistent with lesions usually called 'angina'; they proposed a more appropriate name for the disease: stomatopompholyx haemorrhagica. The authors believe that Balina was the first to describe this condition and suggested the use of the name ROH 1 The awareness of ABH in the field of dermatology and dentistry is very much necessary to avoid misdiagnosis, since this condition spontaneously rupture and heal without any treatment. This case report creates awareness regarding occurrence of the lesion especially on ventral surface of the tongue.…”
Section: Discussionmentioning
confidence: 99%
“…As Kirtschig and Happle pointed out, the term ABH is misleading because most bullae arise in the oral cavity and are not consistent with lesions usually called 'angina'; they proposed a more appropriate name for the disease: stomatopompholyx haemorrhagica. The authors believe that Balina was the first to describe this condition and suggested the use of the name ROH 1 The awareness of ABH in the field of dermatology and dentistry is very much necessary to avoid misdiagnosis, since this condition spontaneously rupture and heal without any treatment. This case report creates awareness regarding occurrence of the lesion especially on ventral surface of the tongue.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the histopathological study in Curran and Rives' case 9 shows ulcerated tissue with inflammatory infiltrate, in which lymphocytes were the most abundant cells, and Aunque el diagnóstico de la ABH es puramente clínico, se debe tener en cuenta la condición sistémica del paciente. Singh et al 14 señalan que una historia de trauma continuo de los dientes a la mucosa puede llevar a un diagnóstico presuntivo de ABH; sin embargo, el diagnós-tico diferencial se hace excluyendo patologías cutáneas, mucosas o sanguíneas, como eritema multiforme, liquen plano, pénfigo, penfigoide, trombocitopenia y la enfermedad de Willebrand.…”
Section: Curran and Rivesunclassified
“…Ангина буллезная геморрагическая (angina bullosa hemorrhagica) -редкое, с доброкачественным течением заболевание, характеризующееся внезапным возникновением на слизистой ротовой полости и/или ротоглотки субэпителиальных пузырей, наполненных геморрагическим содержимым, их появление не связано с системным заболеванием или нарушением гемостаза [1].…”
unclassified
“…Термин «angina bullosa hemorrhagica» был введен N. J. Badham в 1967 г. [1,4]. Ссылаясь на некорректность использования термина «angina», G. Kirtschig и R. Happle в 1994 г. предложили новое название данного заболевания «stomatopompholyx hemorrhagica» [5].…”
unclassified
See 1 more Smart Citation